Audiências de custódia e garantia de direitos humanos: a apresentação em juízo e a prevenção de ilegalidades na região metropolitana de João Pessoa - Silva, Thyago Medeiros da (2020)
The main international human rights treaties represented major advances in the promotion of universal rights inherent to the human person. However, in Brazil, the adaptation to the Human Rights pacts took place late, after years of exception regime. Brazil is one of the world leaders in the ranking of incarceration of people, with prisons that are true deposits of human beings. The violence promoted by the State itself, not only in prison, but during the execution of prisons by its security forces, is something that is present in daily life, especially in the poorest communities. Its Penal Procedure Code was for years based on the supremacy of the ius puniendi over the right to freedom and the presumption of innocence, in a model incompatible with the fundamental precepts of international treaties and its own Constitution. In a contributory action to the paradigm shift, since 2015, the National Justice Council implemented the custody hearings project, in which every person who is deprived of their liberty, must be submitted to the presence of a judicial authority within up to 24 hours. , for analysis and observance of the circumstances and legal aspects of the prison, in addition to facing situations of violence and torture eventually committed by public officials. With this project, Brazil has adapted to the International Human Rights Treaties, even though its legislation still faces congressional inertia regarding the institute's regulations. If, on the one hand, criminal prosecution became more humanized, the custody hearings institute began to suffer systematic attacks from the media, society, representatives of classes linked to public security and parliamentarians against its implementation. In the State of Paraíba, the hearings were implanted in August 2015 initially in its Capital, being gradually expanded to the Counties of the interior. Despite its recent implementation, the institute has already presented impressive results in the Brazilian penitentiary system, results that we will seek to show, based on information obtained from the agencies that act directly in the conduct of hearings, also observing what is in fact proven through the numbers and what is a fallacy among the defenders and critics of the institute. As a research field, we have the city of João Pessoa and the surrounding cities of Cabedelo, Bayeux and Santa Rita, identifying and analyzing the information from the hearings that took place between 2015 and 2020, on various aspects and information, positioning us not only as observers, but with the experience of participating as an enforcer of criminal law and a defender of Human Rights.